River Sedimentation Due to Tin Mining Activities in Bangka Island - Roby Hambali; Lee Sung Tae; Huda Bachtiar; Faisal Ilyas Denansyah; Aditya Pamungkas (Journal of the Civil Engineering Forum, 2024)
Sedimentation in rivers is a major issue of environmental damage in the Kepulauan Bangka Belitung Province. In the last two decades, since tin mining was carried out by the community, massive sedimentation has occurred in the river. The purpose of the study is to investigate the characteristics of sediment materials and the effects of illegal tin mining on river sedimentation on Bangka Island. Sediment characteristics can be seen from the distribution of grain size and specific gravity of the bed sediment material and the concentration of suspended sediments seen from their position along the river. Sediment grain size is classified according to the American Geophysical Union. A total of 45 sediment samples spread across 12 rivers in the district capital area on Bangka Island were collected at the end of the rainy season in 2023, and 4 more samples were added in the dry season of 2023 in the Muntok River. The MPM formula was applied to estimate bedload transport and statistical methods were used to estimate suspended sediment rates. Additionally, the sedimentation rates are estimated based on dependable continuous flow with a probability exceeding 50% (Q50%). The study’s findings indicate that Illegal tin mining in Bangka Island has a major impact on river sedimentation. The particle size distribution of bed material sediments does not align with what is typically found in nature, which often exhibits coarser particles upstream and finer downstream. Similarly, in areas downstream of tin mining operations, the concentration of suspended particles increases significantly, up to 12 times higher than natural conditions.